2020
DOI: 10.3390/ijms21165901
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Diamino-Quinazoline, a Wnt Signaling Inhibitor, Suppresses Gastric Cancer Progression and Metastasis

Abstract: Gastric cancer (GC) is among the most treatment-refractory epithelial malignancies. Aberrant activation of Wnt/β-catenin-signaling has been implicated in a variety of human cancers, including gastric cancer. Here we report that the elevated expression of lymphoid enhancer binding factor 1 (Lef1) is associated with the TNM (tumor– node–metastasis) stage of gastric cancer. Subsequently, 2,4-diamino-quinazoline (2,4-DAQ), a selective inhibitor of Lef1, was identified to suppress the expression of Wnt/β-catenin ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The data from databases and articles showed high expression of β-catenin in gastric cancer at transcription and translation levels [ 47 , 48 ]. This signaling is considered a therapeutic target for gastric cancer treatment [ 49 , 50 ]. Our study shows that the accumulation of nuclear β-catenin promoted proliferation, migration, and invasion of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The data from databases and articles showed high expression of β-catenin in gastric cancer at transcription and translation levels [ 47 , 48 ]. This signaling is considered a therapeutic target for gastric cancer treatment [ 49 , 50 ]. Our study shows that the accumulation of nuclear β-catenin promoted proliferation, migration, and invasion of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Chang et al. found that 2,4-Diaminoquinazoline (2,4-DAQ), a selective inhibitor of LEF1, inhibits the expression of AXIN2, MYC and LGR5 and suppresses the proliferation, migration and invasion of gastric cancer cells ( 93 ). The oral Compound E7386 selectively inhibited the interaction of β-catenin with the β-catenin transcriptional coactivator CREB-binding protein (CBP) and exerted high antitumor activity in a human gastric cancer xenograft tumor model ( 94 ).…”
Section: Molecular Agents Targeting the Wnt Pathwaymentioning
confidence: 99%
“…able to reduce the expression of the β-catenin target genes c-Myc, Axin2 and LGR5, and inhibit the proliferation and viability of CSCs. More importantly, 2,4-DAQ may reduce the migratory and invasive activities of tumor cells, suppress the growth of xenograft tumors and reduce the final tumor weights with few side effects and low drug toxicity (58). DHME, a chemically synthesized derivative of the fungal polyphenol hispolon has been indicated to block signaling of the Wnt canonical pathway by inhibiting the transcriptional activity of the β-catenin/TCF complex.…”
Section: Advances In Anti-colorectal Tumor Therapy Targeting the Cano...mentioning
confidence: 99%